INTEGRATION OF PENAL POLICY AND SOCIAL POLICY IN HANDLING CRIMINAL ACTS OF MURDER ACCOMPANIED BY CHILD RAPE IN SOUTH SUMATRA - Pirmansyah, Redi (Universitas Islam Negeri Raden Fatah Palembang, 2025)
This study examines the implementation of law enforcement against perpetrators of murder accompanied by child rape in the jurisdiction of the South Sumatra Regional Police, using a criminological approach. The main focus is on evaluating the effectiveness of law enforcement, identifying structural and cultural barriers, and applying criminological theories such as Strain, Differential Association, and Routine Activity. The methodology used is an empirical juridical approach with qualitative methods. The findings show that the law enforcement process has been in accordance with positive law provisions, but still faces challenges in the form of limited human resources, lack of coordination between institutions, and the influence of socio-cultural factors. Criminological analysis reveals that these crimes are triggered by social pressure, weak moral control, and open opportunities for crime due to minimal supervision. Therefore, integration between criminal law and social policies is needed in formulating law enforcement strategies for serious crimes involving children as victims